TAMBAL BAN SEPEDA MOTOR YANG ERGONOMIS MENGGUNAKAN ARDUINO UNO - Jusnita (Fakultas Teknik UMRI, 2021)
Tire patch is an activity to repair the tire incompletely only on the part that is leaking. the tire patch tool uses canned gas as a heater, the use of canned gas as a tire heater turns out to have many shortcomings such as the results of the patch being less sticky, the patching time is quite long and it costs a lot of money to buy canned gas. The methodology used in this study is the method of validity, namely testing the hot temperature on an Arduino Uno-based automatic tire patch with a Bluetooth connection. The result of designing an ergonomic motorcycle tire patch tool based on Arduino Uno. The control system tool can work in accordance with its supporting instruments by detecting hot temperatures to operating the device using a Bluetooth connection, there are two types of support systems which are often referred to as software and hardware, so the design process is carried out on both of these supports. The test was carried out 3 times. The first test using a temperature of 80-100 oC takes 3 minutes 28 seconds. The second test using a temperature of 100-120 oC takes 4 minutes 30 seconds with poor results because the results of the patch cannot withstand a large load and cannot withstand being used for too long, while the last or third test uses a temperature of 120-160 oC with the required time. 5 minutes 40 seconds with good patching results.